1997
DOI: 10.1037/0735-7036.111.1.14
|View full text |Cite
|
Sign up to set email alerts
|

Use of landmark configuration in pigeons and humans: II. Generality across search tasks.

Abstract: Pigeons and humans searched for a goal that was hidden in varied locations within a search space. The goal location was fixed relative to an array of identical landmarks. Pigeons searched on the laboratory floor, and humans searched on a table top or an outdoor field. In Experiment 1, the goal was centered in a square array of 4 landmarks. When the spacing between landmarks was increased, humans searched in the middle of the expanded array, whereas pigeons searched in locations that preserved distance and dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
160
6

Year Published

1997
1997
2015
2015

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 143 publications
(184 citation statements)
references
References 26 publications
18
160
6
Order By: Relevance
“…Although pigeons acquired the task, their search behavior appeared to be considerably less accurate and more variable than that found in previous studies in which the absolute distance and bearing from the goal to the landmarks was fixed during training (e.g., Cheng, 1989;Spetch et al, 1997). Numerous procedural differences between this study and previous ones, including a much larger average landmark-to-goal distance, could account for the lower accuracy in the present study.…”
Section: Discussioncontrasting
confidence: 89%
See 2 more Smart Citations
“…Although pigeons acquired the task, their search behavior appeared to be considerably less accurate and more variable than that found in previous studies in which the absolute distance and bearing from the goal to the landmarks was fixed during training (e.g., Cheng, 1989;Spetch et al, 1997). Numerous procedural differences between this study and previous ones, including a much larger average landmark-to-goal distance, could account for the lower accuracy in the present study.…”
Section: Discussioncontrasting
confidence: 89%
“…On trials in which the food and food cup were absent (no-goal trials), the baited finish-box door was opened after 10 sweeping movements were recorded or after a maximum of 10 min. Sweeping movements rather than pecking were used as the index of searching because previous research (e.g., Spetch et al, 1997) indicated that pigeons typically sweep away the bedding first and then peck only upon exposing the food. The sweeping movements were operationally defined as a sideways movement of the beak that resulted in visible displacement of bedding material.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pigeons have been shown to acquire separate landmark-goal vectors independently even in situations involving multiple landmarks (Spetch and Mondloch 1993;Spetch et al 1996Spetch et al ,1997. For example, after learning to find a hidden food goal in the presence of an array of landmarks, search locations on probe tests involving transformations of the landmark array (e.g., expansions of landmark locations or removal of individual landmarks) indicate that pigeons had encoded the vector between one or more individual landmarks and the goal.…”
Section: Discussionmentioning
confidence: 99%
“…One paradigm examines the locus of search for an object presented in a location equidistant to 2, 3 or 4 landmarks, how it changes after expansion of the array of landmarks, and how responses vary between different species. Gerbils (Collett, Cartwright, & Smith, 1986) and pigeons (Spetch, Cheng, & MacDonald, 1996;Spetch et al, 1997) tend to search in locations that maintain the distance and angle to individual landmarks consistent with a model in which the vectors from the landmarks to the objects' locations are stored. Experiments probing a location nearer to one of two landmarks show that the vector from the landmark nearer to the target location is more influential than that from the farther landmark.…”
Section: Behavioral Studies Of Spatial Representation In Humans and Amentioning
confidence: 91%